Review on Internet Addiction in Adolescent: Biomolecular, Hatha Yoga Intervention, COVID-19 Pandemic and Immune Systems - Putu Belly Sutrisna; Cokorda Bagus Jaya Lesmana; I Made Jawi; I Wayan Suka Yasa; I Gusti Bagus Wirawan (Journal of Clinical and Cultural Psychiatry, 2021)
Internet addiction in adolescent during pandemic COVID-19 will be predicted to be increased more than ever. There is need prevention or intervention program to solve this problem. Hatha yoga is considered to be impact mind-body stress relieving exercise found that improve the internet addiction sign and symptoms, but lack of evidence reviews about neurobiology model that effect Hatha yoga and internet addiction. This present review summarizes about Hatha yoga epigenetic mechanism effects could improve in internet addiction. PubMed, ResearchGate and Google scholar have been searched with the following key terms “Internet Addiction and Yoga”, “Yoga and Mental Health”, “Addiction”, “Yoga”, “Addiction and COVID-19”, “exercises and mental health”, “exercise and brain neuroplasticity” from December 2019 up to December 2020. Study in the internet addiction found that significant the expression level of the mRNA of D5 dopamine receptor was significant down-regulated in peripheral blood lymphocytes (PBLs). The literature summarized in this review have shown that Hatha yoga effect through epigenetic process could improve the gene expression mRNA of D5 dopamine receptor in PBLs in the brain in order to improve internet addiction symptoms and sign and active transcription factor Nrf2 to increase the immune system.